Enhanced Evoked Excitatory Transmitter Release in Experimental Neuropathy Requires Descending Facilitation - Gardell, L. R. (J Neurosci, 2003)
Nerve injury-induced afferent discharge is thought to elicit spinal sensitization and consequent abnormal pain. Experimental neuropathic pain, however, also depends on central changes, including descending facilitation arising from the rostral ventromedial medulla (RVM) and upregulation of spinal dynorphin. A possible intersection of these influences at the spinal level was explored by measuring evoked, excitatory transmitter release in tissues taken from nerve-injured animals with or without previous manipulation of descending modulatory systems. Spinal nerve ligation (SNL) produced expected tactile and thermal hyperesthesias. Capsaicin-evoked calcitonin gene-related peptide (CGRP) release was markedly enhanced in lumbar spinal tissue from SNL rats when compared with sham-operated controls. Enhanced, evoked CGRP release from SNL rats was blocked by anti-dynorphin A((1-13)) antiserum; this treatment did not alter evoked release in tissues from sham-operated rats. Dorsolateral funiculus lesion (DLF) or destruction of RVM neurons expressing μ-opioid receptors with dermorphin-saporin, blocked tactile and thermal hypersensitivity, as well as SNL-induced upregulation of spinal dynorphin. Spinal tissues from these DLF-lesioned or dermorphin-saporin-treated SNL rats did not exhibit enhanced capsaicin-evoked CGRP-IR release. These data demonstrate exaggerated release of excitatory transmitter from primary afferents after injury to peripheral nerves, supporting the likely importance of increased afferent input as a driving force of neuropathic pain. The data also show that modulatory influences of descending facilitation are required for enhanced evoked transmitter release after nerve injury. Thus, convergence of descending modulation, spinal plasticity, and afferent drive in the nerve-injured state reveals a mechanism by which some aspects of nerve injury-induced hyperesthesias may occur.